Peningkatan Keterampilan Membaca Pemahaman Peserta Didik Menggunakan Model Cooperative Learning Tipe Jigsaw di Kelas V SDN 15 Batunanggai Kabupaten Agam - Khofifah, Risma; Alwi, Nur Azmi (TSAQOFAH, 2025)
This study is motivated by the low reading comprehension skills of students, teacher-centered learning, and the lack of active participation and critical thinking skills in analyzing information from reading materials. Students also face difficulties in organizing ideas and clearly conveying the content of the reading. The objective of this research is to describe the improvement of reading comprehension skills through the application of the Jigsaw type of Cooperative Learning model. The type of research used is Classroom Action Research (CAR), conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The approach used is qualitative and quantitative, with the research subjects being 20 fifth-grade students at SDN 15 Batunanggai. The results indicate an improvement in various aspects. First, the evaluation of the teaching module increased from 85% in cycle I, meeting 1, to 96% in cycle II. Second, the evaluation of teacher aspects improved from 75% to 96%. Third, the evaluation of student activity increased from 82% to 92%. Fourth, the average score of reading comprehension skills increased from 74.75 to 87.73. Thus, the application of the Jigsaw type of Cooperative Learning model has proven effective in enhancing the reading comprehension skills of elementary school students.